How do we create ASD‐friendly schools? A dilemma of placement. Issue 4 (November 2015) - Goodall, Craig
Abstract : Scope exists within the Northern Ireland (NI) education system to transform mainstream schools into autistic spectrum disorder (ASD)‐friendly environments. The efficacy of mainstream inclusion is discussed prior to discussing the creation of ASD‐friendly schools. The transformation of mainstream school environments is underpinned by concepts such as inclusive pedagogical approach, universal design for learning and learning without limits. These are discussed alongside strategies to enact core inclusive principles of equity, participation and belonging. However, the need for ASD‐specific approaches and schools is also recognised. Our perspectives as educators influence pedagogy, attitudes and approaches to educating autistic children. A social constructivist consciousness is fundamental to moving from deficit SEN rhetoric to creating enabling education for autistic young people. The question of how to achieve this is answered within this article. The use of identity‐first language is preferred by a large proportion of the autism community; therefore the term 'autistic child', rather than 'child with autism', is adopted throughout.